Assessment of the feed additive consisting of Levilactobacillus brevis DSM 21982 for all animal species for the renewal of its authorisation (Marigot Ltd T/A Celtic Sea Minerals) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of Levilactobacillus brevis DSM 21982 as a technological feed additive, silage additive, for all animal species. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. The Panel concluded that the additive remains safe for all animal species, consumers and the environment. Regarding user safety, the additive should be considered as a skin and respiratory sensitiser. No conclusions can be drawn on the eye irritancy potential of the additive. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.